COVID-19 Pandemic and Prisoners - Can, İsmail Özgür and Davas, Hediye Aslı and Biçer, Ümit (The Bulletin of Legal Medicine, 2020)
It is estimated that around 11 million people in the world are detained in prisons. Prisons, detention centers are areas with possible high prevalence of infection due to closed environment with crowded and unsanitary conditions. The problems experienced due to the COVID 19 pandemic in the health examinations and the living conditions of the detainees and convicts will be discussed and ethical approach suggestions published by the Turkish Medical Association will be presented.